Developmental changes in visual short-term memory in infancy: evidence from eye-tracking - Oakes, Lisa M.; Baumgartner, Heidi A.; Barrett, Frederick S.; Messenger, Ian M.; Luck, Steven J. (Frontiers in Psychology, 2013)
We assessed visual short-term memory (VSTM) for color in 6- and 8-month-old infants (n = 76) using a one-shot change detection task. In this task, a sample array of two colored squares was visible for 517 ms, followed by a 317-ms retention period and then a 3000-ms test array consisting of one unchanged item and one item in a new color. We tracked gaze at 60 Hz while infants looked at the changed and unchanged items during test. When the two sample items were different colors (Experiment 1), 8-month-old infants exhibited a preference for the changed item, indicating memory for the colors, but 6-month-olds exhibited no evidence of memory. When the two sample items were the same color and did not need to be encoded as separate objects (Experiment 2), 6-month-old infants demonstrated memory. These results show that infants can encode information in VSTM in a single, brief exposure that simulates the timing of a single fixation period in natural scene viewing, and they reveal rapid developmental changes between 6 and 8 months in the ability to store individuated items in VSTM.